Analisis Akuntabilitas Laporan Keuangan BUMDES Subur Makmur Lestari Desa Wisata Tlogoweru - Sukma Tirta Mayasari; Ernawati Budi Astuti (Jurnal Akuntansi dan Audit Syariah)
The aim of this research was to determine the Accountability of the Financial Reports of Subur Makmur Lestari Village-Owned Enterprises (BUMDES) in the Tlogoweru Tourism Village, Guntur District, Demak Regency, which focuses on Financial Reports and Vertical & Horizontal Accountability. The location of this research is in Tlogoweru Village, Guntur District, Demak Regency. The method used in this research is descriptive qualitative. Sources of data and information needed in this research were obtained from BUMDES financial reports and informants. The data used in this research was collected by conducting interview techniques, observation and taking documentation. Validation of the data used is triangulation. Based on the results of the research carried out, the researchers found that the Financial Report of BUMDES Subur Makmur Lestari was in accordance with SAK EMKM but was not complete, as can be seen from the financial report that was made only the Financial Position Report (Balance Sheet) and Profit and Loss Report while the Notes to the Financial Report had not been made. The accountability of the financial report cannot be said to be accountable because it does not meet the three indicators of financial accountability. Financial integrity has not been maximally integrated, disclosure has not been conveyed to the general public and compliance with statutory regulations has been complied with in accordance with PP Number 11 of 2021 concerning BUMDES.